2013
DOI: 10.4103/1947-2714.122307
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum of rheumatic fever and rheumatic heart disease: A 10 year experience in an urban area of south

Abstract: Background:Rheumatic fever (RF) is an important problem concerning developing countries like India. Rheumatic heart disease (RHD) is one of the most readily preventable chronic diseases.Aim:This study was done to find out the clinical profile, risk factors, compliance with treatment and outcome among RF/RHD cases so as to suggest better case management strategies.Materials and Methods:Clinical records of 51 RF and 71 RHD cases admitted in tertiary care hospitals in Mangalore between 2001 and 2010 were reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
35
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 11 publications
18
35
2
Order By: Relevance
“…[6] Chorea, subcutaneous nodules and erythema marginatum were reported by Joseph N, et al in 13.7%, 7.8% and 5.9% cases, respectively, but contrary to that none of the patients reported all three features in the present study. [7] Chockalingam A et al and other studies reported pericarditis in 37.5% and 41.2%, respectively which is very high as reported by the present study. In initial phase carditis is reported to have a mortality of about 70% and condition can progress to chronic RHD.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…[6] Chorea, subcutaneous nodules and erythema marginatum were reported by Joseph N, et al in 13.7%, 7.8% and 5.9% cases, respectively, but contrary to that none of the patients reported all three features in the present study. [7] Chockalingam A et al and other studies reported pericarditis in 37.5% and 41.2%, respectively which is very high as reported by the present study. In initial phase carditis is reported to have a mortality of about 70% and condition can progress to chronic RHD.…”
Section: Discussionsupporting
confidence: 79%
“…Similar findings were reported by present study using ECHO evaluation. [7] The study done by Melka A et al also reported MR combined with MS as most common lesions in 25.4% patients which supports out findings. [10] But Ravisha MS, et al reported MR to be the most common valvular lesion in RHD patients, which is similar to the findings reported by the present study clinically in 40% patients.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Valvulitis occurs in the mitral valve in 65–75% of cases, aortic valve in 7–30% of cases with the tricuspid valve affected in 10% of cases and involvement of the pulmonary valve being rare 2 6–9…”
Section: Rheumatic Heart Diseasementioning
confidence: 99%
“…37 What is clear, however, is that the use of secondary prophylaxis, even in clinically diagnosed RF and RHD is poor worldwide, averaging only ≈30% of patients eligible for penicillin. 69,70 It is therefore incumbent on proponents of mass echocardiographic screening for RHD to conduct prospective randomized controlled studies to provide the burden of proof that this strategy would result in superior clinical outcomes, 71 although some have pointed out that the logistics and ethics make this an unlikely proposition.…”
Section: Would Any Intervention Significantly Alter the Natural Progrmentioning
confidence: 99%